2019
DOI: 10.1111/risa.13389
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study Evaluating the Risk of Infection from Middle Eastern Respiratory Syndrome Coronavirus (MERS‐CoV) in a Hospital Setting Through Bioaerosols

Abstract: Middle Eastern respiratory syndrome, an emerging viral infection with a global case fatality rate of 35.5%, caused major outbreaks first in 2012 and 2015, though new cases are continuously reported around the world. Transmission is believed to mainly occur in healthcare settings through aerosolized particles. This study uses Quantitative Microbial Risk Assessment to develop a generalizable model that can assist with interpreting reported outbreak data or predict risk of infection with or without the recommende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 59 publications
(116 reference statements)
0
90
1
3
Order By: Relevance
“…As such, health care providers may become exposed to aerosols theoretically able to permeate N95 FFRs. Increasing air-exchange per hour (ACH) or HEPA filtration of room air represent potential supplemental mitigation measures (5). Air exchange rates varies between imaging suites, depending on ventilation, air circulation and room configuration.…”
Section: Protection Of Radiology Staffmentioning
confidence: 99%
“…As such, health care providers may become exposed to aerosols theoretically able to permeate N95 FFRs. Increasing air-exchange per hour (ACH) or HEPA filtration of room air represent potential supplemental mitigation measures (5). Air exchange rates varies between imaging suites, depending on ventilation, air circulation and room configuration.…”
Section: Protection Of Radiology Staffmentioning
confidence: 99%
“…The idea that saliva droplets could represent an important source of infection and a suitable sample for diagnosis was highlighted in 2003 during the SARS outbreak ( Wang et al 2004 ). Analogous considerations were made for the Middle Eastern respiratory syndrome coronavirus (MERS-CoV) outbreak ( Adhikari et al 2019 ). Similarly, the eruption of the new pandemic and its severe course have drawn the attention of researchers to these issues.…”
Section: The Detection Of Sars-cov-2 In Salivamentioning
confidence: 99%
“…[2][3][4][5] Mounting and convincing evidence has shown that, in addition to the major route of transmission of COVID-19 of droplet transmission and contact with contaminated fomites, aerosols can be another route of transmission. [12][13][14][15] The SARS-CoV-2 virion, with a size of 0.07 to 0.09 mm, has the potential to be transmitted as an aerosol and might behave similar to its close relatives of SARS and Middle East respiratory syndrome. 16 van Doremalen et al 17 recently reported that viable SARS-CoV-2 virion could be detected in aerosols for 3 hours.…”
Section: Covid-19 Effects On Colorectal Practicementioning
confidence: 99%